Menganalisis Efektivitas Pembelajaran Berdiferensial pada Mata Pelajaran Ilmu Pengetahuan Sosial di Sekolah Menengah Pertama - Ahdar, Ahdar; adriani, adriani (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2024)
Differentiated learning is a flexible method that provides opportunities for students to learn according to their interests and needs. This study aims to determine the effectiveness of implementing this method and its impact on social studies learning outcomes at SMP Negeri 1 Parepare. The study used a quasi-experimental method with a quantitative approach. The population consisted of all 374 seventh grade students, while the sample was 68 students, 34 students each from the experimental class (VII.1) and control class (VII.2). Data were collected through observation, documentation, and tests, then analyzed using normality, homogeneity, and t-tests. The results showed that (1) differentiated learning was effective with an average N-Gain Score of 75.5% and (2) there was a significant increase in learning outcomes. The t value of 6.256 with df 66 and significance 0.001 (0.05) indicated that H0 was rejected. Thus, the application of this method has been proven to be able to improve the learning outcomes of seventh grade students at SMP Negeri 1 Parepare.